PENGARUH PEMBERIAN EDUKASI DAN SIMULASI DAGUSIBU TERHADAP PENGETAHUAN MASYARAKAT TENTANG PENGELOLAAN OBAT RASIONAL DI TINGKAT KELUARGA - Diza Fathamira Hamzah; Teuku Muhammad Rafsanjani (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
The irrational use of drugs at the family level indirectly contributes to increase morbidity and mortality rates, which in turn reflects the community health status. Therefore, it is important to conduct interventions in the form of education and simulations on how to obtain, use, store, and dispose of drugs in order to make proper self-medication efforts successfull so as to minimize the risk of ineffective treatment and inefficiency in treatment costs.This study aims to examine the effect of providing education and simulation on public knowledge about rational drug use at the family level. This research is a quasi-experimental research with one group pre and post test design. The sample was drawn using a total sampling technique where all the mothers of the family were drawn as sample in this study totaling 30 people. Data was collected using a questionnaire. Knowledge measurement was carried out before and 2x24 after the education and simulation were given. Data analysis was performed by using paired T-test with 95% confidence interval.The results showed that there was an increase in  average score of knowledge before and after the provision of education and simulation by 5.34%. The provision of education and simulation has a significant effect of public knowledge about rational drug use (p-value 0.000).Keywords: Health Promotion, Health Status, Knowledge, Rational Use of Drugs, Self-Medication